"Kinda Like a Man and a Woman Thing": The Construction and Reification of Gender Hegemony in a Women's Prison. (October 2017) - Gorga, Allison
This article examines how a hegemonic gender regime is constructed and maintained by persons with bodies marked as female. Using semistructured interviews with prisoners in a women's prison, I demonstrate how a gender dichotomy is replicated among a population of primarily women in which certain styles of masculinity and femininity are posited as complimentary and situated within a gender hierarchy. Prisoners cocreated and maintained an ideal definition of masculinity—"studs"—that centered on status, resources, and heteronormative sexual patterns, whereas femininities—"femmes"—were subordinated and their gender practices devalued. Studs were subjected to greater levels of social control and were stigmatized for stepping out of the prescribed bounds of normative stud behavior. Although several respondents also contested or challenged hypermasculinities in the prison, this contestation often reified gender and sexual expectations for studs. The presence of such a gender regime in a women's prison suggests that the global system of masculine dominance is an obstinate social construct.